Potential of Lacto-Gypsum as an Amendment to Build Soil Quality - Bondi, Giulia; Fenton, Owen; Sawdekar, Parikshit; Keane, Hilda; Wall, David P. (Frontiers in Sustainability, 2021)
Strategies for amendment use on agricultural soils are needed to help build resilience against potential soil threats. Gypsum amendments are commonly applied to soils to improve soil quality and nutrient supply. However, the sustainability of supply and environmental safety of some gypsum sources is uncertain. This study aimed to i. characterise a new by-product, lacto-gypsum, derived from a dairy whey side stream over a one year pilot production cycle, and to assess the temporal variability of the raw lacto-gypsum form and stability of its physico-chemical and compositional properties when stored under three potential storage regimes. Results show that lacto-gypsum compared favorably with conventional equivalents in terms of nutrients and trace element concentrations and represents an environmentally safe gypsum material free of contaminants. Storage form did not affect its main physico-chemical characteristics over time and the raw lacto-gypsum remained stable up to 20 days when stored at 4C. However, the lacto-gypsum had very low pH in contrast to conventional gypsum. In general this new lacto-gypsum represents a potentially suitable product for use as soil amendment or as an acidification agent for animal slurry to reduce ammonia gas emissions during land-spreading. However, further evaluation of this by-product in real scenarios is required.